Incidental Detection of Elastofibroma Dorsi With 68Ga-FAPI-46 and 18F-FDG PET/CT in a Patient With Esophageal Cancer. (February 2021) - Hayrapetian, Artineh; Girgis, Mark D.; Yanagawa, Jane; French, Samuel W.; Schelbert, Heinrich R.; Auerbach, Martin S.; Czernin, Johannes; Calais, Jeremie
Abstract : Abstract: A 71-year-old man underwent 18 F-FDG and 68 Ga-FAPI-46 PET/CT for initial staging prior to surgery of a squamous cell carcinoma of the lower esophagus under the prospective study NCT04147494. Both scans showed increased uptake in the mid and distal esophagus without evidence of metastatic disease. A soft tissue right infrascapular mass with mild 18 F-FDG and moderate 68 Ga-FAPI-46 uptake was incidentally found. The patient underwent robotic-assisted Ivor-Lewis esophagectomy and excision of the right infrascapular mass. Histopathology of the right chest wall mass confirmed the diagnosis of elastofibroma.